Sensory, Emotional and Cognitive Contributions to Anxiety in Autism Spectrum Disorders - South, Mikle; Rodgers, Jacqui (Frontiers in Human Neuroscience, 2017)
Severe symptoms of anxiety add substantial additional burden to many individuals diagnosed with Autism Spectrum Disorder (ASD). Improved understanding of specific factors that contribute to anxiety in ASD can aid research regarding the causes of autism and also provide targets for more effective intervention. This mini-review focuses on emerging evidence for three concepts that appear to be related to each other and which also strongly predict anxiety in ASD samples. Atypical sensory function is included in the diagnostic criteria for ASD and is likely an important contributor to anxiety. Difficulties understanding and labeling emotions (alexithymia), although a co-morbidity, may arise in part from atypical sensory function and can lead to confusion and uncertainty about how to respond to social and emotional situations. Intolerance of uncertainty (IU) describes people who have a particularly hard time with ambiguity and is known to be a key mechanism underlying some anxiety disorders. While evidence for linking these ideas is to date incomplete, we put forward a model including each concept as a framework for future studies. Specifically, we propose that IU is a critical mediator for anxiety in ASD, and explore the relationships between sensory function, alexithymia, and IU. We further explore the role of the medial prefrontal cortex (mPFC) in regulating emotional response, in connection with limbic and insula-based networks, and suggest that disrupted integration in these networks underlies difficulties with habituation to strong emotional stimuli, which results in an enhanced perception of threat in many people with ASD. Behavioral and biologically-based treatments for anxiety in ASD will benefit from attending to these specific mechanisms as adjunct to traditional interventions.